MENINGKATKAN KUNJUNGAN WISATAWAN NUSANTARA DI BALI BIRD PARK MELALUI ANALISIS STRATEGI BAURAN PEMASARAN - Dendy Baskara Permana, I Dewa Made; Sudiarta, I Nyoman; Kristianto, Yohanes (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2023)
Tourism is defined as a variety of tourist activities supported by various facilities and services provided by society, entrepreneurs, and governments. Bali is an icon of tourism in Indonesia. One of the famous tourist attractions in Bali is Bali Bird Park. This tourist attraction was closed for three months, that resulted in a decrease in the number of tourist visits. With the decrease tourist’s visit, management of tourist attractions must carry out strategies, especially in marketing, so that tourist visits, especially from Nusantara’s tourists, to the Bali Bird Park remain stable even though it is still in the new normal era. This research uses qualitative data analysis techniques, included the SWOT matrix and created a SWOT diagram, to determine the company’s strategic position. The technique of sample determination used purposive sampling with a total of 123 respondents. The results showed that the total score of Strength was 1.86 and Weakness was 0.55. For Opportunities was 1.94 and Threats was 1.17. From the total subtraction between strength and weakness, the result is 1.31, while the total subtraction between opportunity and threats is 0.77. The SWOT diagram shows that the company’s strategic position is in quadrant I, which means in a growth-oriented position, so the marketing strategy that can be implemented is an aggressive strategy.